Unveiling authoritarian repression of insurgency in José Ricardo Morales’ play Los culpables - Valdivia Martin, Pablo (2025)
This article offers a critical analysis and discussion of José Ricardo Morales’ play Los culpables (1964), which may encourage critical reflection on Chile’s political reality concerning the repression of anti-authoritarian movements. The study aims to demonstrate the relevance of Morales’ play in contemporary Chile. This play serves as a case study to explore the playwright’s ideas regarding the repressive and authoritarian practices employed by a military government against citizens labeled insurgents, ultimately aiding in the examination of the Chilean context. Since this play represents various historical events linked to authoritarianism, particularly World War II and Francoism, we argue that it foreshadows the implementation of authoritarian practices by the state in Chilean society, including the state’s criminalization of protesters, insurgents, and anti-authoritarian movements in the 1960s and 1970s, as well as the criminalization of social movements during the recent 2019 Social Outbreak civil protests.